Morgiana Based on a Story by Aleksandr Grin - Herz, Juraj; Kucera, Jaroslav; Janzurová, Iva; Abrham, Josef; Cepek, Petr (Second Run, 2010)
Often described as the 'last' film of the Czech New Wave, Juraj Herz's delirious tale of terror is a fantastical and surreal phantasmagoria of dark desires and splintered minds. Morgiana, based on a short story by Aleksandr Grin, (the 'Russian Poe'), is the story of two sisters, Klára and Viktoria who live a life of decadent excess stranded somewhere between the mid-19th and early 20th century. Klára is blonde and beautiful, whilst Viktoria is ugly, sadistic, bursting with hate and jealousy - and hatches a terrible revenge by slowly poisoning her more popular sister. As the poison takes hold, Klára begins to lose grip on her sanity ... [www.dvdbeaver.com]